Hedge Funds & Their Impact on the Indian Capital Market - Tibrewal, Saket (2008)
Hedge funds are an investment structure that manages a private unregistered investment pool. They use several strategies like leveraging, long, short and derivative positions to generate high returns and hedge probable market risks. Hedge funds restrict their investment base to high net worth individuals rather than allowing the general public to invest in them.